2016
DOI: 10.1007/s11884-016-0344-9
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Overactive Bladder on US Public Health

Abstract: Overactive bladder (OAB) is a highly prevalent symptom condition that affects millions of US men and women. Not only can the symptoms of OAB be very bothersome, but OAB can have significant detrimental effects on many aspects of individuals’ lives, representing a particularly impactful health burden to quality of life and productivity. Estimates of the individual and societal costs for the management of OAB continue to rise, particularly as effective treatments remain elusive. As such, OAB represents a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
104
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 32 publications
1
104
1
Order By: Relevance
“…Idiopathic overactive bladder syndrome (OAB) represents a significant public health burden, as it affects one out of six U.S. adults, accounts for $66 billion in total annual U.S. societal costs, and can be difficult to treat effectively . While the etiology of OAB remains unclear, a substantive body of animal and ex vivo research suggests that increased afferent nerve activity (including activation of normally quiescent c‐fibers) and altered CNS processing of excitatory signals contribute to OAB pathophysiology .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Idiopathic overactive bladder syndrome (OAB) represents a significant public health burden, as it affects one out of six U.S. adults, accounts for $66 billion in total annual U.S. societal costs, and can be difficult to treat effectively . While the etiology of OAB remains unclear, a substantive body of animal and ex vivo research suggests that increased afferent nerve activity (including activation of normally quiescent c‐fibers) and altered CNS processing of excitatory signals contribute to OAB pathophysiology .…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic overactive bladder syndrome (OAB) represents a significant public health burden, as it affects one out of six U.S. adults, accounts for $66 billion in total annual U.S. societal costs, and can be difficult to treat effectively. 1 While the etiology of OAB remains unclear, a substantive body of animal and ex vivo research suggests that increased afferent nerve activity (including activation of normally quiescent c-fibers) and altered CNS processing of excitatory signals contribute to OAB pathophysiology. 2,3 However, a reliable means to assess such changes in individuals with OAB has remained elusive, and thus whether and how these pathophysiologic mechanisms might contribute to clinical OAB manifestations, impart resistance to primary and secondary therapies, and influence treatment outcomes are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…International populationbased studies have reported prevalence rates of OAB approximately 12% (6,7) and it rises 17% in patients aged 40 and over (2). OAB symptoms are not only disturbes patients but also have a significant negative impact on many aspects of the lives of individuals who represent a particularly effective health burden in terms of quality of life and productivity (3). It is known that obesity is a strong risk factor for OAB.…”
Section: Introductionmentioning
confidence: 99%
“…Overactive bladder (OAB) has a deeply negative impact on quality of life, with higher economic costs for patients and the society. 1 The prevalence of this condition is between 11.8% and 16.5% in the USA and Europe, estimated to reach 24% by 2020. [2][3][4] Behavioral and pharmacologic therapies (antimuscarinics or oral ß3-adrenoceptor agonists) are considered the first and second-line therapy.…”
Section: Introductionmentioning
confidence: 99%